Desenvolvimento de um sistema embarcado para aquisição de sinais eletrocardiograma e eletromiograma - Contardi, Uriel Abe (2022)
This work aims to develop a portable embedded system, with rechargeable battery and support for Bluetooth and USB communication to collect electrocardiography and surface electromyography signals. In this way, the work approaches the dimensioning: of the electronic instrumentation circuits for conditioning the biosignals, processing circuits and energy management and digital circuits for reading and sending the signals. and the realization of the mechanical design for better use of the device. In addition, the work involves the development of a graphical interface in python, using PyQt5, to visualize the signals in real time. Finally, the functioning of the platform is illustrated through the collection of electrocardiogram and electromyogram signals from the author of the work, the platform proved to be functional and the results obtained were satisfactory.